2015
DOI: 10.1016/j.ijhydene.2015.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stable Cu-MCM-41 nanocatalysts for H2 production with high selectivity via steam reforming of methanol

Abstract: Available online xxxKeywords: Steam reforming Cu-MCM-41 Metal loading One-pot synthesis Catalyst deactivation N 2 O chemisorption a b s t r a c t High surface area MCM-41 containing copper catalysts (with different loading from 5 to 20 wt%) were synthesized using one-pot procedure for steam reforming of methanol (SRM) studies. A variety of techniques including BET, XRD, TGA-DSC, TEM, EDX, ICP-OES, H 2 -TPR, N 2 O chemisorption and EPR were used to characterize the physical and chemical properties of catalysts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 69 publications
6
37
0
Order By: Relevance
“…With the introduction of TiO 2 into the CuO/TS‐20 precursor, the high‐temperature peak disappears. The CuO/TS‐20 precursor shows an evident peak near 543 K. With the further addition of TiO 2 , the CuO/TS‐40 precursor shows two more intense peaks, which shift to lower temperature, corresponding to the reductions of highly dispersed supported CuO nanoparticles (518 K) and small bulk‐like CuO particles (531 K), respectively. Compared to the CuO/TS‐40 precursor, besides the peaks at 513 and 524 K, the CuO/TS‐60 precursor also shows a high‐temperature peak at 569 K, which is attributed to the CuO‐TiO 2 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…With the introduction of TiO 2 into the CuO/TS‐20 precursor, the high‐temperature peak disappears. The CuO/TS‐20 precursor shows an evident peak near 543 K. With the further addition of TiO 2 , the CuO/TS‐40 precursor shows two more intense peaks, which shift to lower temperature, corresponding to the reductions of highly dispersed supported CuO nanoparticles (518 K) and small bulk‐like CuO particles (531 K), respectively. Compared to the CuO/TS‐40 precursor, besides the peaks at 513 and 524 K, the CuO/TS‐60 precursor also shows a high‐temperature peak at 569 K, which is attributed to the CuO‐TiO 2 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Smaller Cu nanoparticles with strong interaction with the support are useful to increase the stability of the catalysts during the reaction [63], and the preparation procedure can have a significant impact on the final Cu dispersion. For instance, Zhou et al [14] have shown that by using a fractionated precipitation method to prepare a Cu/ZrO 2 catalyst, the Cu dispersion can be increased-although remaining low compared to other systems [4,97]-with a significant gain in stability.…”
Section: Cu/zro2mentioning
confidence: 99%
“…Among them, siliceous MCM‐41 is an important class of a one‐dimensional (1D) hexagonal porous materials in which an amorphous SiO 2 network is interposed . The large surface area of MCM‐41 (>1,000 m 2 /g), its specific pore volume (up to 1.3 mL/g), and its high thermal stability make it suitable for dispersing the active sites and hence boost catalytic activity . Generally, MCM‐41 exhibits mild acidity and weak hydrogen bonding, but active catalytic sites can be generated by the incorporation of organic or inorganic species into their structures.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The large surface area of MCM-41 (>1,000 m 2 /g), its specific pore volume (up to 1.3 mL/g), and its high thermal stability make it suitable for dispersing the active sites and hence boost catalytic activity. [6,7] Generally, MCM-41 exhibits mild acidity and weak hydrogen bonding, but active catalytic sites can be generated by the incorporation of organic or inorganic species into their structures. Frequently imidazole, piperazine, aluminum atom, boron, and some transition metals such as Zn, Ti, and Fe can be employed to achieve this.…”
Section: Introductionmentioning
confidence: 99%